On the sensitivity of root and leaf phenology to warming in the Arctic - Laura Radville; Eric Post; David M. Eissenstat (Arctic, Antarctic, and Alpine Research, 2018)
Temperature is commonly assumed to act as the primary constraint on the timing of plant growth, and strong advances in plant phenology have been seen with recent atmospheric warming. The influence of temperature on the timing of root growth, however, is less clear, and controls on root phenology are not well understood. The influence of temperature on above- and belowground phenology is particularly important in the Arctic, where most plant biomass is belowground and warming is occurring at a higher rate than in other ecosystems. We examined the influence of experimental warming on graminoid and shrub communities in the Arctic in southern west Greenland. We found that warming since 2012 did not advance the timing of aboveground seasonal dynamics during two years or belowground seasonal dynamics during three years. We suggest that growing-season temperature may no longer be the primary constraint on plant phenology at this site, and plant phenological responses to future warming at the site may consequently be weaker.